(untitled) (1993)
A major concern by fisheries biologists and managers has been the perception that hatchery fish are inferior to wild fish, and belief that the hatchery fish tend to degrade natural populations. These perceptions are not without foundation, but the problems are the fault of how we have managed hatcheries, and not with either the concept or the potential which hatcheries can offer. The oversight that we have demonstrated consistently throughout our history of fisheries management has been to ignore the fact that fish populations are an integral component in a complex environmental system. If we neglect the requirements that populations have, and hence the traits they allow them to synchronize their life history with specific environmental constraints, failure is certain. Although appropriate technology is the key in producing healthy hatchery fish, the critical component for success of the hatchery concept is the seed stock used for propagation. Every effort must be made to work with the negative gene pool and avoid contamination from other brood sources to maintain stock synchrony with the environment.
Keywords: hatchery programs